Garlic Extract Alleviates Trastuzumab-Induced Hepatotoxicity in Rats Through Its Antioxidant, Anti-Inflammatory, and Antihyperlipidemic Effects - Mousa AM; Soliman KEA; Alhumaydhi F; Almatroudi A; Al Rugaie O; Allemailem KS; Alrumaihi F; Khan A; Rezk MY; Aljasir M; Alwashmi ASS; Aba Alkhayl FF; et al. (Dove Medical Press, 2021)
Ayman M Mousa,1,2 Khaled EA Soliman,3,4 Fahad Alhumaydhi,5 Ahmad Almatroudi,5 Osamah Al Rugaie,3 Khaled S Allemailem,1,5 Faris Alrumaihi,5 Arif Khan,1 Mohamad Y Rezk,3,6 Mohammad Aljasir,5 Ameen SS Alwashmi,5 Faris F Aba Alkhayl,5 Aqel S Albutti,7 Hanan S Seleem3,8 1Department of Basic Health Sciences, College of Applied Medical Sciences, Qassim University, Buraydah, 51452, Saudi Arabia; 2Department of Histology and Cell Biology, Faculty of Medicine, Benha University, Benha, 13518, Egypt; 3Department of Basic Medical Sciences, College of Medicine and Medical Sciences, Qassim University, Unaizah, 51452, Saudi Arabia; 4Department of Forensic Medicine and Clinical Toxicology, Sohag Faculty of Medicine, Sohag University, Sohag, 82524, Egypt; 5Department of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Buraydah, 51452, Saudi Arabia; 6Department of Medical Physiology, College of Medicine, Zagazig University, Al-Sharquia, 44519, Egypt; 7Department of Medical Biotechnology, College of Applied Medical Sciences, Qassim University, Buraydah, 51452, Saudi Arabia; 8Department of Histology and Cell Biology, Faculty of Medicine, Menoufia University, Shebin Elkoum, EgyptCorrespondence: Fahad AlhumaydhiDepartment of Medical Laboratories, College of Applied Medical Sciences, Qassim University, Buraydah, Saudi ArabiaEmail f.alhumaydhi@qu.edu.saBackground: Trastuzumab is a new biological drug that has been used to treat breast and gastric cancer; however, its cardiotoxicity and hepatotoxicity limit its use. Garlic has antioxidant, anti-inflammatory, antihyperlipidemic, and anticancer effects. The present study aimed to evaluate the effects of garlic on trastuzumab-induced hepatotoxicity in a rat model.Methods: Twenty rats were divided into four equal groups as vehicle control (G1), garlic (G2), trastuzumab (G3), and trastuzumab+garlic (G4). All rats were sacrificed after eight weeks of treatment, followed by blood collection and excision of liver tissues for further analyses. The liver specimens were processed for histopathological (HP), immunohistochemical (expression of TNF-α and PCNA), immunofluorescent expression of Chk2 and p53, biochemical, and flow cytometry investigations to evaluate the extent of hepatocyte injury. The biochemical analysis was conducted for the activity of tissue antioxidants (GPX1, CAT, and SOD2), serum lipid profile, and liver enzymes, whereas ROS was performed by flow cytometry.Results: The results revealed remarkable structural changes in hepatocytes of G3 with significant increases in the numbers of inflammatory cells and positive PCNA cells, area % of collagen fibers, and immuno-expression of TNF-α, as well as a significant reduction in the nuclear expression of Chk2. In addition, significant reductions were noticed in the antioxidant enzymes (SOD2, CAT, and GPX1) activity of G3. In contrast, the levels of lipid profile tests (triglycerides, total cholesterol, LDLC, and HDLC), liver enzymes (ALT, AST, and ALP), and ROS revealed significant increases in rats of G3. Likewise, garlic administration in G4 restored all mentioned changes to their average levels deviated by trastuzumab.Conclusion: Based on the current results, garlic demonstrates hepatoprotective effects against trastuzumab-induced toxicity in rats. The study suggested for the first time that the coadministration of garlic with trastuzumab for treating breast or gastric cancer can augment their efficacy with minimal toxicity.Keywords: trastuzumab, aqueous garlic extract, cancer, hepatotoxicity, oxidative stress, liver enzymes